Therapeutic and Prognostic Implications of Immune-Related Adverse Events in Advanced Non-Small-Cell Lung Cancer - Daniello, Lea; Elshiaty, Mariam; Bozorgmehr, Farastuk; Kuon, Jonas; Kazdal, Daniel; Schindler, Hannah; Shah, Rajiv; Volckmar, Anna-Lena; Lusky, Fabienne; Diekmann, Leonore; Liersch, Stephan; Faehling, Martin; et al. (Frontiers in Oncology, 2021)
Introduction PD-(L)1 inhibitors have improved prognosis of non-small-cell lung cancer (NSCLC), but can also cause immune-related adverse events (irAEs) that complicate management. Methods We analyzed NSCLC patients receiving PD-(L)1 inhibitors from 2012 to 2020 in a German academic center. Results IrAE showed comparable frequencies in stage IV (198/894 or 22%) vs. III (14/45 or 31%, p = 0.15), after anti-PD-(L)1 monotherapy vs. chemoimmunotherapy (139/483 vs. 58/213, p = 0.75), and across treatment lines. In stage IV, irAE occurred after 3.1 months in median, affected multiple organs (median 2) in 27/894 patients and were associated with PD-L1 positivity (25 vs. 14%, p = 0.003), lower neutrophil-to-lymphocyte ratios (29 vs. 17%, p < 0.001 for NLR dichotomized at 5), better ECOG status (26 vs. 18% for 0 vs. 1, p = 0.004), but not related to age, sex, smoking and palliative radiotherapy. Two hundred thirty two irAEs occurred mostly in endocrine glands (4.9%), lungs (4.4%), the musculoskeletal system (4.2%), colon (4.1%), liver (3.7%), and skin (2.6%), while pneumonitis was most frequent with durvalumab following definitive chemoradiation (16% or 7/45, p < 0.01). IrAE severity was grade 1 in 11%, 2 in 41%, 3 in 36%, and 4 in 11% events, while two were lethal (<1%, myocarditis and pneumonitis). Therapy was suspended in 72%, while steroids were initiated in 66% and complemented by other immunosuppressants in 6%, with longest treatment duration for rheumatic events (mean >3 months), and average cumulative prednisone doses >700 mg for all organs, except for skin. Patients developing irAE had longer progression-free (PFS) and overall survival (OS) in multivariable 12/14-week landmark analyses including ECOG status, treatment line, treatment type, PD-L1 TPS, and NLR (median PFS 17 vs. 10 months, HR = 0.68, p = 0.009; median OS 37 vs. 15 months, HR = 0.40, p < 0.001), regardless of grade. OS was longest with skin (95% at 2 years) and shortest with pneumonitis, hepatitis, neurologic, and cardiologic irAE (38, 37, 28, and 0% at 2 years, p < 0.001). Conclusions Approximately one-fourth of immunotherapy-treated NSCLC patients develop irAEs, most of which necessitate treatment suspension and steroids. Despite more frequent occurrence with PD-L1 positive tumors, lower NLR, and better ECOG PS, irAEs are independently associated with longer survival, especially when affecting the skin. Lethality is below 1%.